2012
DOI: 10.1002/elsc.201100088
|View full text |Cite
|
Sign up to set email alerts
|

Microbial trans‐glutaminase enhances the physical and mechanical properties of depigmented wool

Abstract: This study investigates the effects of enzymatic treatment with microbial transglutaminase (m-TGase) on the physical and mechanical properties of the depigmented wool yarns. Coarse pigmented wool yarns were treated with iron (II) followed by depigmentation with both oxidative and oxidative-reductive chemicals. The depigmented wool yarns were then treated with m-TGase to reduce the negative effects of the harsh chemicals. Diverse features of the wool yarns, including: tensile strength, elongation, color, diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The wool treated with bentonite and enzyme has the characteristic peaks in the spectrum as a consequence of their presence. However, a decrease in the peak intensity as well as shifting to the lower wavelength corresponded to the N–H (at 3300–3600 cm −1 ) [ 49 ]. In details, amide band, arising from N–H stretching vibration coupled with –OH groups via hydrogen bonding [ 50 ], was observed at wave numbers of 3270 and 3260 cm −1 for the wool sample treated with m-TGase and m-TGase/bentonite, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The wool treated with bentonite and enzyme has the characteristic peaks in the spectrum as a consequence of their presence. However, a decrease in the peak intensity as well as shifting to the lower wavelength corresponded to the N–H (at 3300–3600 cm −1 ) [ 49 ]. In details, amide band, arising from N–H stretching vibration coupled with –OH groups via hydrogen bonding [ 50 ], was observed at wave numbers of 3270 and 3260 cm −1 for the wool sample treated with m-TGase and m-TGase/bentonite, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It is well-known that m-TGase is a unique enzyme capable of catalyzing acyl transfer reactions by introducing covalent cross-links between glutamine and lysine in proteins and peptides [ 49 , 54 , 55 ]. Amino acids or alkyl ammonium ions act as a compatibilizing agents to treat clay structures since they exchange easily with ions between the silicates layers of clay [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…The surface changes of wool fibers treated with various concentrations of m-TGase and alum were investigated, and the SEM images are presented in Figure 2a-c. Our results showed that by increasing m-TGase concentration, some surface damages appeared so that some of the scales were damaged and led to less cuticle surface ( Figure 2b). This phenomenon probably was because of alkali condition, which is obtained as a result of more cross-link reaction by adding more m-TGase [43]. Indeed, m-TGase affected wool fiber by following cross-link reaction between glutamine and lysine, which are present in wool structure: Therefore, it is essential to use the enzyme in a suitable amount.…”
Section: Surface Morphologymentioning
confidence: 99%
“…Since wool fibers are protein-rich fibers, m-TGase could be used to alter the characteristics of wool keratin [29,30,[43][44][45]. 4.…”
mentioning
confidence: 99%
“…The properties of wool fabrics modified by transglutaminases are summarized in Table S4. Transglutaminase treatment showed the ability to recover tensile strength after previous chemical or protease treatments (Cortez et al 2005;Cardamone 2007;Du et al 2007;Gaffar-Hossain et al 2008;Ge et al 2009;Zhang et al 2010;Montazer et al 2011Montazer et al , 2012. Other effects include (Cui et al 2008).…”
Section: Transglutaminases For Wool Modificationmentioning
confidence: 99%